Relationship between Tahajud prayer frequency and memory in the elderly in brebes district - Fuad, Wijayanti; Basuki, Rochman; Afiah, Dieska Laudza (South East Asia Nursing Research, 2024)
In the elderly, as age increases, there will of course be a decline in organs and body functions which can disrupt daily activities. This can be caused by the aging process, one of which is characterized by a decline in cognitive function. One of the declines in cognitive function in the elderly is memory loss. Memory decline can be prevented with spiritual activities, one of which is the midnight prayer. This study aims to analyze the relationship between the frequency of midnight prayers and memory in the elderly in the Brebes Regency. This research method is quantitative analytical observational using a cross-sectional design. The research subjects were elderly people in RT 002/RW 004 Dukuhturi Village, Bumiayu District, Brebes Regency. The total sample that met the inclusion criteria was 35 respondents. The research was carried out in February 2024. The measuring instruments used were the Tahajud prayer questionnaire and the digit span questionnaire. The analytical test used in this research is the chi-square test. The results of the chi-square test showed a p-value of 0.004 (< 0.05), which means that there is a relationship between the frequency of midnight prayers and memory in the elderly in the Brebes Regency. The results of the analysis concluded that there was a significant relationship between the frequency of midnight prayers and memory in the elderly in the Brebes Regency.